PRINSIP GOVERNANCE DALAM PENGELOLAAN PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA BANGLAS BARAT KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI TAHUN 2014-2016 - Sukarman "; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is motivated target PAMSIMAS village election in the village of Banglas Barat years 2014-2016 in accordance with the decree of the minister of public works decree No. 79 / Kpts / DC / 2013 on stipulation district / city target PAMSIMAS. Implementers program PAMSIMAS at the district level conducted by the planning office and the department of public health office of human settlements POKJA AMPL is incorporated in regency Kepulauan Meranti, while implementers at the village level is done by the village government, KKM, SATLAK, BPSPAMS and community facilitator team. The study aims to determine the principles of governance in the management of Banglas Barat PAMSIMAS in the village and the factors that affect the management of PAMSIMAS program. The type used in this research is descriptive research with qualitative research approach. Type of research data is primary data and secondary data. Data collection techniques in this study is documentation and interviews. Technical analysis of the data used is descriptive qualitative data analysis.The results showed that the principle governance in the management program in the village PAMSIMAS Banglas Barat has not run optimally. It is seen from some of the principles governance of accountability and the rule of law can not be applied by managers BPSPAMS PAMSIMAS particularly in operational and maintenance phase PAMSIMAS assets. inhibiting factor which is greater in terms of both internal and external. The right solution to overcome the problems in the management of PAMSIMAS Village Banglas Barat is particularly BPSPAMS PAMSIMAS manager must be optimized in applying the principles of governance in coordination with all parties involved in the program PAMSIMAS and supported by the budget of the village government and local government.Keywords: principles Governance, management PAMSIMAS, and integration